A new algorithm for single residue digit error correction in redundant residue number system - Chang, Chip-Hong (2015)
This paper presents a new algorithm for the correction of single residue digit error in Redundant Residue Number System. The location and magnitude of error can be extracted directly from a minimum size lookup table. This is made possible by the introduction of a new syndrome, which is proven to be unique for every different residue digit error with two criteria imposed on the choice of redundant moduli. The erroneous residue digit can be corrected by deducting the error digit retrieved from the lookup table indexed by the syndrome. Our proposed algorithm compares favorably against existing single residue digit correction algorithms, and is more amenable to hardware implementation.